Recreio escolar de crianças do ensino fundamental: contexto educativo para participação, brincadeiras e aprendizagens - Maximo, Heliny de Carvalho (2020)
We start from the consideration of the school playground, as space and time inserted in the school curriculum that allows the insertion in the playful cultures and languages of contemporary childhoods. We understand that children need to be heard and participate in their learning processes at school. Therefore, we carried out the research “with” the children, aiming to identify, describe and understand how the children's participation and learning takes place in the playful experiences in the the school playground time, of the elementary school. For this, we also propose: identifying what children play in the schoolyard; to explain how they use the the school playground time; map the spaces they explore there and present the interactions between children and between them and adults. Qualitative in nature, the research included a bibliographic survey and insertion in the field, in the school playground time. As instruments, we highlight the use of drawings and field diaries: participant observation and semi-structured interviews, conducted with fourteen girls. In the results, we identified how much children enjoy the school playground, but disapprove of the little time available to play. The girls point out that they learn in the playful dynamics, revealing creativity to adapt to the various conditions proposed and interact with their friends, getting closer by sharing snacks, games and toys. In addition to showing a lot of affectivity in interpersonal relationships, the girls still share projections for improve the school playground time aiming to enrich this school space. In this way, we put these learnings and children's participation on the scene, inviting the sensitization of new perspectives to this context that promotes education.